Gender-Based Violence: How Children and Women are Protected? (Law Research Review Quarterly, 2021)
Right is an element inherent in man since the man is still in the womb until he died. In society, efforts are often made to fulfill human rights by everyone, and because the fulfillment of those rights, results in the violation of rights against other individuals. Speaking about human rights there are now many cases of human rights violations against women and children. The most common case is violence in women and children. Violence against women today is not only a matter of individuals, but also national and even international problems. Violence against women can happen anywhere and by anyone. It is certainly a concern. In addition to the issue of human rights violations against women, there are also violations of human rights against children. The future of the nation lies in the welfare of children. Currently there are many violations of children's rights. Many children are abandoned to become street children, wage workers even become beggars. This research is intended to analyze the gender-based violence and the protection of women and children in Indonesia.